SYSTEM DESIGN INSURANCE POLICY ISSUED REPORTS PT ASURANSI JIWA EKA LIFE - Fitria Fitria; Drs. H. Soetirto Sadikin, MA (Jurnal Sistem Informasi, 1997)
To be able to compete with other Life Insurance, PT Eka Life Insurance should attempt to provide better services to its customers. With good service facilities expected number of customers will continue to grow. Computerized information system is one way to achieve maximum service so that data processing becomes more effective and efficient. By way of interviews and observations to the field about the current system, and the results were analyzed. This study produced a description that Life Insurance is in great need of the computerized information system to assist the smooth operation, administration, and preparing reports.Â